Ranolazine improved left ventricular diastolic functions and ventricular repolarization indexes in patients with coronary slow flow - Oksen, Dogac; Aslan, Muzaffer; Ozmen, Emre; Yavuz, Yunus Emre (Frontiers in Cardiovascular Medicine, 2023)
Introduction Coronary slow flow (CSF) is a condition commonly encountered during angiography. Recent studies have shown the adverse effects of CSF on left ventricular diastolic functions. CSF reportedly increases the novel ventricular repolarization parameters. Ranolazine is a preparation with a prominent anti-anginal activity that has positive effects on anti-arrhythmic and diastolic parameters. In this context, this study was carried out to investigate the effects of ranolazine on left ventricular diastolic functions and repolarization in patients with CSF. Material and methods Forty-six patients with CSF and 29 control subjects were included in the patient and control groups, respectively. Both groups received ranolazine for one month and were evaluated using 12–lead electrocardiography, conventional echocardiography, and tissue Doppler imaging at the baseline and after one month of ranolazine treatment. Results Corrected P, QT dispersion, and Tp-e interval values were significantly higher in the patient group than in the control group. There was a significant decrease in isovolumic relaxation time (IVRT) and deceleration time (DT) values after the ranolazine treatment compared to the baseline values in the patient group but not the control group. A significant increase was observed in the mean E and A velocities and the mean E/A ratio after the ranolazine treatment compared to the baseline values in the patient group. Additionally, there was a significant difference between the Tp-e interval and corrected P dispersion values measured after the ranolazine treatment compared to the baseline values in the patient group but not in the control group. Conclusion This study's findings demonstrated that ranolazine positively affected impaired diastolic functions and repolarization parameters, particularly in patients with CSF.